Better Management in Real Estate Industry from Quality Perspectives - A Case in Real Estate Industry in Vietnam - DAT, PHAM MINH (The journal of contemporary issues in business and government, 2021)
There are several factors affecting enhancing management capabilities of real estate companies in Vietnam. For instance: management of quality of construction and real estate projects, better organization of human resources, better practices of corporate governance, etc. With OLS regression method, the article suggests a total quality management perspective for managing real estate activities and propose recommendations for macro policies that affect firm performance. For instance, exchange rate policy need to be in favor of USD/VND just little bit while inflation policy need to be controlled well. Moreover, Applying TQM not only improves the quality of products and services but also improves the operational efficiency of the whole system thanks to the principle of always doing the right thing the first time. Limitation of the research is that the model can be expanded for other markets.